The Integral Nature of Worship and Evangelism: Insights from the Wesleyan Tradition - Chilcote, Paul Wesley (The Asbury journal, 2006)
This essay explores the fundamental relationship between worship and evangelism through the lens of the hymns and writings of Charles Wesley. After laying a biblical foundation for the integral nature of worship and evangelism based upon Acts 2:46-47 and examining the image of paideia (instruction through action) in Heb. 12:9-10 as a concept implying their integration, the author describes the liturgy of the worshiping community as the primary matrix of evangelistic ministry. The call of the prophet Isaiah (6:2-8) reveals a paradigm related to worship that instructs our understanding of evangelism as well. All true worship and faithful evangelism begins with the acknowledgement of God. The experience of repentance and forgiveness liberate God's people and enables them to be ambassadors of reconciliation and restoration. Charles Wesley's hymns illustrate each of these critical themes. Worship shapes the people of God and forms them into an evangel-bearing community for the life of the world as they proclaim and embody the Good News of God's love through Christ.